Alkoxyallenes as Starting Materials for the Syntheses of Natural Products - Schmiedel, Volker M.; Reissig, Hans-Ulrich (Current Organic Chemistry, 2019)
Alkoxyallenes are easily available and versatile building blocks for the preparation of a variety of natural products (terpenes, polyketides, alkaloids, amino acids, carbohydrates etc.) originating from different classes. The synthetic use of the three allene carbon atoms frequently follows the “normal” reactivity pattern showing that alkoxyallenes can be regarded as special enol ethers. Additions of alcohols or amines to alkoxyallenes form vinyl-substituted O,O- or N,O-acetals that are frequently used in ring-closing metathesis reactions. This methodology delivers crucial heterocyclic units of the target compounds. Enantioselective additions provide products with high enantiopurity. Alternatively, an “Umpolung” of reactivity of alkoxyallenes is achieved by lithiation at C-1 and subsequent reaction with electrophiles, such as alkyl halides, carbonyl compounds, imines or nitrones. High stereoselectivity of the addition step can be achieved by substrate control or auxiliary control. The high diastereo- or enantioselectivity is transferred to the subsequent acyclic or cyclic products. The cyclization of primary addition products occurs efficiently under mild conditions and provides functionalized dihydrofuran, dihydropyrrole or 1,2-oxazine derivatives. These are valuable intermediates for the synthesis of a variety of heterocyclic natural products. Nazarov cyclizations or gold catalyzed rearrangements allow the synthesis of five- and six-membered carbocyclic compounds that are also used for natural product synthesis.
Keywords: ring-closing metathesis